Determination of the diagnostic efficiency of contrast-enhanced ultrasound in the diagnosis of liver metastases of colorectal cancer - K. V. Kozubova; E. A. Busko; S. S. Bagnenko; E. V. Kostromina; R. A. Kadyrleev; I. Kh. Kurganskaya; L. N. Shevkunov (Digital Diagnostics, 2022)
ABSTRACT